Desafios para o ensino primário em Angola a partir do depoimento de professores da rede pública - André, Inocente Coronel Muendo (2017)
This research intends to identify this research intends to identify the positive and negative aspects of the reality of primary schools Angola was the semi-structured interview technique of gathering information; characterization of respondents, where were placed the subject of research and its delimitations judiciously, followed by the analysis of the content, with the elaboration of categories of information that has been collected. After the analysis of the interviews, research has shown that primary education in Angola still faces great difficulties even though it was installed the educational reform. The teachers ' reports show many difficulties and challenges to be overcome since the own infrastructure, teaching materials and even the policies directed to the question of the training of a qualified teaching to meet the demand of primary school students and the curriculum that guides the elementary school. Many teachers have not yet assimilated the issue of Monodecency for lack of preparation. It is the responsibility of the Ministry of education, together with the Government review and make new diagnoses in order to combat such weaknesses that primary education faces and hear these teachers about the reality experienced in the day-to-day activities of teachers, in order to map goals that allow a quality education to all education in Angola